2020
DOI: 10.11646/zootaxa.4809.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular data provide new insights into the phylogeny of Cladonotinae (Orthoptera: Tetrigoidea) from China with the description of a new genus and species

Abstract: Considerable effort has been devoted to elucidating the phylogenetic relationships of tetrigides. However, there is still no commonly accepted phylogenetic hypothesis. Therefore, the phylogenetic relationships among some subfamilies remain unclear; e.g., Cladonotinae is a controversial group, in which the phylogenetic relationships between genera and the boundaries of some of the included genera are unclear, causing some of the taxa to be difficult to identify. Therefore, an in-depth phylogenetic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 1,166 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Tetriginae was monophyletic in all analyses with current species and the subfamily was the more recently diverged group. This was also supported by previous phylogenetic studies ( Jiang, 2000 ; Fang et al, 2010 ; Zhang et al, 2020 ). In addition, the results from four trees showed that S. spicupennis of Metrodorinae clustered near the clade Tetriginae, Bolivaritettix lativertex was closely related to C. japonicus of Scelimeninae.…”
Section: Resultssupporting
confidence: 90%
“…Tetriginae was monophyletic in all analyses with current species and the subfamily was the more recently diverged group. This was also supported by previous phylogenetic studies ( Jiang, 2000 ; Fang et al, 2010 ; Zhang et al, 2020 ). In addition, the results from four trees showed that S. spicupennis of Metrodorinae clustered near the clade Tetriginae, Bolivaritettix lativertex was closely related to C. japonicus of Scelimeninae.…”
Section: Resultssupporting
confidence: 90%
“…tonkinensis occupied the most basal position, followed by the second branch, S. borneensis , which was positioned as a sister group to the remaining Tetrigoidea (posterior probability, PP = 1). These data, suggesting that T. tonkinensis is the earliest species within Tetrigoidea, followed by S. borneensis , which was consistent with the results of the molecular phylogenetic analyses conducted by earlier study showing that S. borneensis is an earlier species within Tetrigoidea (Zhang et al 2020 ). Moreover, sixteen tetrigid species were grouped in a clade with strong support (PP = 1), which suggested Tetrigidae is monophyletic.…”
supporting
confidence: 92%
“…This subfamily currently contains 3 tribes and 25 known genera worldwide; the genus Saussurella Bolivar includes twelve species endemic to Southeast Asia (Deng 2016 ; Zha et al 2020 ). However, there is little information on the systematic position of S. borneensis within the Tetrigidae (Zhang et al 2020 ). To date, no mitochondrial sequence has been reported for the Batrachidinae (NCBI, last visited on May 2021).…”
mentioning
confidence: 99%
“…This diverse and polyphyletic family includes altogether 314 species assigned to 74 genera ( Cigliano et al 2022 ). Most genera require revision and are not adequately classified in the Tetrigidae system ( Zhang et al 2020 ). Within the subfamily Cladonotinae , several monophyletic tribes exist, such as Caribbean Choriphyllini ( Choriphyllum Serville, 1838 and Phyllotettix Hancock, 1902), African Xerophyllini (including leaf-like Acmophyllum Karsch, 1890, Seyidotettix Rehn, 1938, Trypophyllum Karsch, 1890, Xerophyllum Fairmaire, 1846), and Asian Cladonotini ( Hymenotes Westwood, 1837, Holoarcus Hancock, 1909, Dolatettix Hancock, 1907).…”
Section: Resultsmentioning
confidence: 99%